2021
DOI: 10.1177/10996362211050919
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour in shear and compression of polyurethane foam at elevated temperature

Abstract: This paper presents an experimental investigation about the effect of elevated temperature on the mechanical properties of two polyurethane (PUR) foams, with densities of 40 kg/m3 and 93 kg/m3. The experimental campaign included shear and compressive tests over a temperature range of 20°C–200°C, performed to assess the degradation of the mechanical properties of the PUR foams with temperature. To validate the diagonal tension shear test method adopted in this investigation, a numerical study was also performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Additionally, Linul et al (2017) [ 26 ] reported that the best density regarding energy absorption is 100 kg/m . A density around this value was also studied in the works of Liu et al (2019) [ 27 ], Mazzuca et al (2021) [ 28 ], and Iqbal et al (2022) [ 29 ].…”
Section: Methodsmentioning
confidence: 92%
“…Additionally, Linul et al (2017) [ 26 ] reported that the best density regarding energy absorption is 100 kg/m . A density around this value was also studied in the works of Liu et al (2019) [ 27 ], Mazzuca et al (2021) [ 28 ], and Iqbal et al (2022) [ 29 ].…”
Section: Methodsmentioning
confidence: 92%
“…An alternative explanation is that the increase in temperature reduces the modulus of elasticity of the polyurethane material, leading to more rapid collapse of the cells within the foam, and thereby increasing the voltage for the same reason that higher frequencies increase voltage. While we cannot report accurate values of temperature dependence for the foam being tested in this study, various studies of rigid polyurethane foams have demonstrated reductions in the modulus of 25% or more for temperature increases from 20 °C to 70 °C (the temperature increase observed for compression at a steady frequency of 45 Hz in Figure 8 ) [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical performance of these foams was serious damaged when they were subjected to elevated temperatures or fire. All these drawbacks mentioned above greatly limited the application of syntactic foams ( McKenna and Hull, 2016 ; Mazzuca et al, 2022 ). Considerable attempts have been made by researchers to develop high-performance syntactic foams.…”
Section: Introductionmentioning
confidence: 99%